Goniometer control - Vasiliev, G.P.; Kovalenko, G.D.; Maslov, N.I.; Ovchinnik, V.D.; Shulika, M.Yu.; Shliakhov, I.N.; Yalovenko, V.I. (Вопросы атомной науки и техники, 2021)
The control unit for the goniometer has been developed and manufactured. The unit includes four independent programmable stepper motor control channels, three logical channels for analyzing the state of limit switches and a power supply. Powerful field-effect transistors of the company International Rectifier are used as controlled power switches. To generate output signals and communicate with a computer, an ATmega328 microprocessor is used in each control channel. This channel design allows you to control almost any type of stepper motors, you only need to replace the control program. The software is written using the WinAVR package which has a General Public License. Data transfer between the computer and the unit is carried out via the USB interface. Розроблено та виготовлено блок управління гоніометром. До складу блоку входять чотири незалежних програмованих канали керування кроковими двигунами, три логічних канали аналізу стану кінцевих вимикачів та джерело електроживлення. В якості керованих силових ключів використовуються потужні польові транзистори фірми International Rectifier. Для формування вихідних сигналів і зв’язку з комп’ютером у кожному каналі управління використовується мікропроцесор ATmega328. Така побудова каналу дозволяє управляти практично будь-яким типом крокових двигунів, потрібно тільки замінити програму управління. Програмне забезпечення написано з використанням пакета WinAVRб який має General Public License. Передача даних між комп’ютером та блоком здійснюється за допомогою USB-інтерфейсу. Разработан и изготовлен блок управления гониометром. В состав блока входят четыре независимых программируемых канала управления шаговыми двигателями, три логических канала анализа состояния конечных выключателей и источник электропитания. В качестве управляемых силовых ключей используются мощные полевые транзисторы фирмы International Rectifier. Для формирования выходных сигналов и связи с компьютером в каждом канале управления используется микропроцессор ATmega328. Такое построение канала позволяет управлять практически любым типом шаговых двигателей, требуется только заменить программу управления. Программное обеспечение написано с использованием пакета WinAVR, имеющего General Public License. Передача данных между компьютером и блоком осуществляется по USB-интерфейсу.